2011
DOI: 10.1203/pdr.0b013e3182242deb
|View full text |Cite
|
Sign up to set email alerts
|

Periconceptional Events Perturb Postnatal Growth Regulation in Sheep

Abstract: Periconceptional undernutrition and twin conception alter intrauterine growth and metabolism and are associated with later adverse metabolic outcomes. The contribution of postnatal growth to these outcomes is less well defined. We investigated whether maternal periconceptional undernutrition or twin conception altered postnatal growth regulation in ways that could lead to metabolic disease. Single and twin offspring of ewes undernourished (UN) from 61 d before until 30 d after mating, fed to achieve and mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
1
19
0
1
Order By: Relevance
“…Periconceptional undernutrition in sheep has been associated with changes in fetal growth trajectory [19], hypothalamic-pituitary-adrenal (HPA) [2] and somatotropic [20] axis function, disordered postnatal growth regulation [4], and altered glucose-insulin [7] and HPA axis [5] function in adulthood. Here, we report that despite the relatively small effects on size at birth, postnatal growth trajectory, and final body size, periconceptional undernutrition results in significantly altered body composition in a sexually dimorphic manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Periconceptional undernutrition in sheep has been associated with changes in fetal growth trajectory [19], hypothalamic-pituitary-adrenal (HPA) [2] and somatotropic [20] axis function, disordered postnatal growth regulation [4], and altered glucose-insulin [7] and HPA axis [5] function in adulthood. Here, we report that despite the relatively small effects on size at birth, postnatal growth trajectory, and final body size, periconceptional undernutrition results in significantly altered body composition in a sexually dimorphic manner.…”
Section: Discussionmentioning
confidence: 99%
“…Postnatally, growth regulation is altered [4], and changes in endocrine function become apparent with increasing age, including suppressed hypothalamic-pituitary-adrenal (HPA) [5] and leptin-insulin [6] axis function and impaired glucose tolerance [7]. One possible mechanism that might contribute to this postnatal metabolic risk after periconceptional undernutrition is altered body composition, for example, if the early nutritional insult also resulted in increased relative fat mass and/or decreased lean mass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of effect on gross morphology at birth, however, does not necessarily reflect the impact of early gestational intervention upon long-term growth, development and health in the offspring (Wu et al 2006) as we have previously reported. In sheep, peri-conceptional undernutrition does not necessarily result in altered birthweight but has been associated with altered fetal growth trajectory and altered post-natal growth, metabolic and endocrine regulation (Jaquiery et al 2011). The post-natal effects of similar periods of peri-conceptional undernutrition in the bovine are less well understood.…”
Section: Birthweightmentioning
confidence: 99%
“…For example, in studies of formula feeding vs. breast feeding, or comparisons between high and low protein containing infant formulas, rates of obesity and altered insulin dynamics have largely been attributed to a difference in growth rates between groups, assuming overnutrition, accelerated growth rates, and change in body composition to be causative factors (11)(12)(13). One difficulty with this assumption, however, is the poor correlation between energy intake and growth rate in the immediate postnatal period, particularly after intrauterine insult (14). It may be that intrauterine factors influence both early growth rate and later metabolism more strongly than postnatal caloric intake, and that dietary composition per se influences the development of physiological pathways and organ development independently of early growth rate.…”
Section: Introductionmentioning
confidence: 99%